Penerapan Metode Multilevel Queue Antrian Pendaftaran Pasien pada Klinik Talang Kelapa Berbasis Android - Nurul Huda; Novriyadi Novriyadi (LPPM UBHINUS MALANG, 2023)
Information regarding online patient registration is urgently needed by the people of Palembang City. But in reality, there are still many registrations that have not done online registration at clinics and hospitals. So we need an application that makes it easier for people to register online. The author chose the Talang Kelapa Clinic as a place that needs to register online so that people can easily register at the Talang Kelapa Clinic. The implementation of the application uses the Multilevel Queue (MLQ) Method. This method is the basic idea of an algorithm based on a process priority system. So, each process can be grouped based on priority. The use of appropriate and varied applications in the online registration process can make it easier to register online and can reduce the attitude of users who have to register manually.